2020
DOI: 10.1242/bio.055541
|View full text |Cite
|
Sign up to set email alerts
|

Uncharted routes: exploring the relevance of auxin movement via plasmodesmata

Abstract: Auxin is an endogenous small molecule with an incredibly large impact on growth and development in plants. Movement of auxin between cells, due to its negative charge at most physiological pHs, strongly relies on families of active transporters. These proteins import auxin from the extracellular space or export it into the same. Mutations in these components have profound impacts on biological processes. Another transport route available to auxin, once the substance is inside the cell, are plasmodesmata connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 143 publications
0
19
0
Order By: Relevance
“…PIN proteins, which are known to be involved in bud activation, might therefore also play roles in the less studied process of postactivation growth. Interplay between cell-cell communication and hormonal networks have already been reported in other contexts (Paterlini, 2020).…”
mentioning
confidence: 63%
“…PIN proteins, which are known to be involved in bud activation, might therefore also play roles in the less studied process of postactivation growth. Interplay between cell-cell communication and hormonal networks have already been reported in other contexts (Paterlini, 2020).…”
mentioning
confidence: 63%
“…Recent studies have demonstrated clearly that diffusion through plasmodesmata is a key component of the auxin transport machinery, both affecting the auxin distribution and, most importantly, contributing to plant phenotypes (Paterlini, 2020). Manipulating auxin diffusion through plasmodesmata (using lines that regulate callose levels) has been shown to affect auxin distributions, phototropism, lateral root emergence and leaf hyponasty.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Obviously, most of the genes in auxin signaling pathway in C. maxima leaves exposed to cold stress were inhibited, which generally are obligated to cell elongation, division, cycle, and growth [13,73]. Auxin is an endogenous small molecule with an incredibly large impact on plant growth and and response to stress in concert with other hormonal pathways [74][75][76]. The Auxin response factor (ARF), Gretchen Hagen 3 (GH3), and Auxin/indole-3-acetic acid (Aux/IAA), small Auxin-Up RNA (SAUR) gene families, are key components of the auxin signaling pathway, and function as regulators of plant growth and response to stress [77,78].…”
Section: Plant Hormone Signaling Involved In Cold Stressmentioning
confidence: 99%